(untitled) (Journal of Atomic and Molecular Sciences, 2017)
Ionization occurs when strong femtosecond laser pulses propagate in nitrogen gas. The ionized nitrogen molecules are in ground electronic state as well as excited electronic states. In this paper, we study the polarization distribution of the fluorescence emission corresponding to the transition of N_2^+ (B_2Σ_u^+ → X^2Σ_g^+). It is found that the fluorescence polarization exhibits an anisotropic angular distribution relative to the pump laser polarization, which can be attributed to the permanent alignment caused by angular-dependent ionization of neutral nitrogen molecules in strong femtosecond laser fields. The permanent alignment characterized by ‹cos^2θ› reaches 3 ⁄ 7 in our experiment where θ is the angle between the molecular axis and the pump laser polarization.